Energy allocation optimization of the gas-cooled space nuclear reactor. (September 2021) - Qin, Hao; Wang, Chenglong; Tian, Wenxi; Qiu, Suizheng; Su, Guanghui
Highlights: Energy allocation optimization of gas cooled space nuclear reactor is conducted. A set of models of direct Brayton cycle coupled with radiator are established. Mass of heat pipe radiator is unacceptable for megawatt space applications. Liquid droplet radiator is promising to be used in large power space reactors. Abstract: The development of the space vehicles puts forward higher requirements on the energy supply, and the megawatt gas-cooled space nuclear reactors are promising to satisfy the demand. The energy allocation optimization on the space nuclear reactors takes critical part in the system design. The optimization between the energy conversion efficiency and radiator mass of the gas-cooled space nuclear reactor is conducted and analyzed. The models of direct Brayton cycle, heat pipe radiator, and liquid droplet radiator are established. The working performance of the thermodynamic cycle coupled with heat pipe radiator (HPR) and liquid droplet radiator (LDR) are obtained respectively, and compared. The area and weight of the HPR increases linearly with the radiant power. The calculation results show that, for space nuclear reactors adopting HPR, decreasing the coolant temperature at the reactor core outlet ( T 1 ) from 1500 K to 1200 K will increase the specific surface area from 1200 m 2 /MW to about 3000 m 2 /MW with the same energy conversion efficiency. The radiant power of the LDR can be regulated by operation mode with the radiator weight remains unchanged. The mass of LDR is only about 10% of HPR for case with electricity power P e = 0.5 MW, T 1 = 1500 K, showing significant advantage in the mass optimization. This paper may contribute to the energy management and allocation optimization of the gas-cooled space nuclear reactor.